1985
DOI: 10.1021/bi00333a027
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary structure has little influence on spin states in mixed-spin human methemoglobins

Abstract: A key feature of the Perutz stereochemical model for cooperativity in hemoglobin is a strong coupling between quaternary structure and the spin state of the heme iron [Perutz, M. F. (1979) Annu. Rev. Biochem. 48, 327-386]. While this coupling appears to be present for carp azide methemoglobin, it should also be present for all liganded forms of human methemoglobin that exhibit a thermal high-spin in equilibrium low-spin equilibrium. To test this hypothesis, we have measured the changes in spin equilibria upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
4
12
0
Order By: Relevance
“…However, they do demonstrate that this is still an open question which warrants further investigation. That this is the case is also indicated by the results of Philo and Dreyer [19]. These authors report only modest values of AAG" for the thiocyanate derivative of human hemoglobin as a result of P6-inositol addition.…”
Section: Aag" = -R T Ln-= R T L N ( P+ -P?s 2 ) X ( P K -$ )mentioning
confidence: 70%
“…However, they do demonstrate that this is still an open question which warrants further investigation. That this is the case is also indicated by the results of Philo and Dreyer [19]. These authors report only modest values of AAG" for the thiocyanate derivative of human hemoglobin as a result of P6-inositol addition.…”
Section: Aag" = -R T Ln-= R T L N ( P+ -P?s 2 ) X ( P K -$ )mentioning
confidence: 70%
“…In contrast, the smaller effect of bezafibrate alone continues to increase as the pH is lowered. Philo and Dreyer (1985) reported that the nitrite derivative of human hemoglobin was unstable in their hands. To control for the possibility of time-dependent changes, spectra of solutions of this derivative were examined as a function of time.…”
Section: Resultsmentioning
confidence: 99%
“…When Philo and Dreyer repeated the magnetic experiments with both human HbA and the abnormal human Hb Kansas in which the R-structure is destabilized by the rupture of a crucial hydrogen bond, they found no significant rise in the paramagnetic susceptibility of either Hb on switching their azide-met derivatives from R to T and concluded that this rise was a peculiarity shown only by fish Hbs (40). This seemed improbable in view of the extensive homology of the heme surrounds and subunit contacts in all vertebrate Hbs.…”
Section: Changes In Spin Equilibrium Of the Ironsmentioning
confidence: 99%